Contexts Articulation for Teaching in Management: Competitive performance of organizations - Serralvo, Francisco Antonio; Romaro, Paulo (European Public & Social Innovation Review, 2025)
Introduction: The Articulation of Contexts for Teaching in Administration - Competitive Performance of Organizations Project is part of the studies developed by the University to create new practices and pedagogical structures for undergraduate and graduate courses at the University. Structured around three stages, the project aimed to consolidate students' knowledge of the fundamentals of the competitive performance of organizations. Methodology: The study used participant observation to examine the impact of new teaching methods on student engagement and learning at a Brazilian university. Researchers collected data through classroom observations, engagement reports, field notes, and interviews. Thematic analysis identified vital factors influencing engagement, such as teaching methods and classroom interactions. Results-Discussions: The project integrated subjects to analyze businesses and consumers, develop various products, end with the CRM proposal in the companies studied, provide practical learning, and prepare students for the market. Conclusions: Students applied theory to real problems through the expected products, developing critical thinking, collaborative skills, and management competencies. Disciplinary integration and effective practice consolidated an effective teaching model aligned with market demands.